Biomechanics of osteochondral impact with cushioning and graft Insertion: Cartilage damage is correlated with delivered energy. (17th May 2018) - Su, Alvin W.; Chen, Yunchan; Dong, Yao; Wailes, Dustin H.; Wong, Van W.; Chen, Albert C.; Cai, Shengqiang; Bugbee, William D.; Sah, Robert L.
Abstract: Articular cartilage is susceptible to impact injury. Impact may occur during events ranging from trauma to surgical insertion of an OsteoChondral Graft (OCG) into an OsteoChondral Recipient site (OCR). To evaluate energy density as a mediator of cartilage damage, a specialized drop tower apparatus was used to impact adult bovine samples while measuring contact force, cartilage surface displacement, and OCG advancement. When a single impact was applied to an isolated (non-inserted) OCG, force and surface displacement each rose monotonically and then declined. In each of five sequential impacts of increasing magnitude, applied to insert an OCG into an OCR, force rose rapidly to an initial peak, with minimal OCG advancement, and then to a second prolonged peak, with distinctive oscillations. Energy delivered to cartilage was confirmed to be higher with larger drop height and mass, and found to be lower with an interposed cushion or OCG insertion into an OCR. For both single and multiple impacts, the total energy density delivered to the articular cartilage correlated to damage, quantified as total crack length. The corresponding fracture toughness of the articular cartilage was 12.0 mJ/mm 2 . Thus, the biomechanics of OCG insertion exhibits distinctive features compared to OCG impact without insertion, with energy delivery to the articular cartilage being a factor highly correlated with damage.